Penerapan Metode AHP Untuk Membantu Siswa Memilih Jurusan Yang Tepat Di SMK - Frieyadie Frieyadie; Surya Mahendra Ramadhan (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Students of junior high school who are planning to continue their education to vocational school (SMK) must decide the choice, to the field or what majors will be chosen to continue their education later. And this is something quite difficult to decide by most junior high school students, especially those who do not have many references and seek information related to vocational education. Most of them are less mature to choose the majors that exist according to their ability, due to enough new students who fail in the middle of the road when they have been accepted in Vocational High School (SMK). The result of analysis of Analytical Hierarchy Process result calculation stated that the chosen alternative and most appropriate with criteria is Broadcast. With AHP results obtained from 3 respondents who then calculated and obtained the final result that Broadcast excels with a percentage value of 43% versus Accounting 27% and 31% Office Administration. Globally the most important factor prioritized in the selection of majors is the test score with a weighted value of 0.473 or 47% and the most priority majors are Broadcast majors with a score of 47%. The Analytical Hierarchy Process method can help schools in particular to determine some issues regarding the selection of majors. Because the AHP method is a method whose main input is human perception.